The effects of boredom and distress tolerance on problematic internet use among university students - Ayleah Paz Sim Aquino; Patricia Joseph Kimong (Fakulti Psikologi dan Pendidikan, 2021)
The COVID-19 pandemic has been associated with increased psychological distress. As a coping strategy, individuals spend more time on the internet, especially university students who are at greater risk for problematic Internet use (PIU). Although boredom has been identified as a significant predictor of PIU and psychological stressor in COVID-19, studies of boredom in the context of PIU is limited in local and overseas studies. There is also a critical gap on whether distress tolerance reduces the likelihood of PIU among individuals. The study investigates the relationships between boredom, distress tolerance, and PIU, along with the effects of boredom and distress tolerance on PIU among university students. A conceptual framework on the relationship between boredom, distress tolerance, and PIU is presented based on flow theory and the model of distress tolerance. This framework could contribute towards a better understanding of PIU by explaining possible predictors and the role of boredom and distress tolerance in Internet use. The evidence of PIU among university students can aid in the early detection of PIU and encourage appropriate intervention strategies. Mental health practitioners should also be aware of boredom as a psychological stressor and assist clients in developing distress tolerance as a self-regulation strategy.